KEADAAN SANITASI PEMUKIMAN DI DESA TEGAL HARUM KECAMATAN DENPASAR BARAT TAHUN 2022 - Komang Ayudia Satya Amrita; Anysiah Elly Yulianti; Nengah Notes; I Nyoman Purna (Poltekkes Kemenkes Denpasar, 2023)
Tegal Harum Village is one of the villages in West Denpasar District which has 8 banjars, namely Tegal Sari, Sapta Bumi, Bhuana Mertha, Sanga Agung, Cemara Agung, Buana Kubu, Sari Buana and Asta Buana. A house is a building that functions as a residence and a means of fostering a family. The number of heads of families residing in Tegal Harum Village is 3,356 households. This study aims to determine the state of residential sanitation in Tegal Harum Village, West Denpasar District in 2022 using the 2002 Ministry of Health questionnaire, from the questionnaire there are 3 aspects of the assessment consisting of the house component, sanitation facilities and occupant behavior by observing and interviewing the head of the family. This study uses a descriptive study because the researcher wants to know theexisting situation. Based on the results of surveys and observations a conducted sample of 68 families. The results of house the do not meet the requirements of 39 houses with a percentage of 57% and meet the requirements of 29 houses with percentage of 43%. Suggestions for residents in the TegalHarum Village environment are expected to pay more attention to the sanitation of their homes.